Cranial radiation for pediatric T‐lineage acute lymphoblastic leukemia: A systematic review and meta‐analysis. Issue 10 (22nd July 2014) - Kelly, Michael J.; Trikalinos, Thomas A.; Dahabreh, Issa J.; Gianferante, Matthew; Parsons, Susan K.
<x xml:space="preserve">Abstract</x> There are heterogeneous approaches to cranial radiation therapy (CRT) for T‐lineage acute lymphoblastic leukemia (T‐ALL). We performed a systematic review of studies that specified a radiation strategy and reported survival for pediatric T‐ALL. Our analysis included 62 publications reporting 78 treatment groups (patient n = 5844). The average event‐free survival (EFS) was higher by 6% per 5 years (P < 0.001). Adjusting for year, EFS differed by radiation strategy. Compared to the reference group (CRT for all) which had a year‐adjusted EFS of 65% (95% confidence interval, CI: 61–69%) the adjusted EFS was significantly worse (rate difference (RD) = −9%, 95% CI: −15 to −2%) among studies that used a risk‐directed approach to CRT (P = 0.004). The adjusted EFS for the other strategies were not significantly different compared to the reference group: CRT for central nervous system positive patients only (RD = −3%, 95% CI: −14 to 7%, P = 0.49); CRT omitted for all patients (RD = 5%, 95% CI: −4 to 15%, P = 0.33). CRT may not be necessary with current chemotherapy for T‐ALL. These findings, however, are susceptible to bias and caution should be applied in drawing conclusions on the comparative effectiveness of alternative CRT strategies. Am. J. Hematol. 89:992–997, 2014. © 2014 Wiley Periodicals, Inc.